Transapical transcatheter aortic valve implantation in patients with aortic diseases. (12th March 2021) - Useini, Dritan; Beluli, Blerta; Christ, Hildegard; Schlömicher, Markus; Ewais, Elias; Patsalis, Polykarpos; Haldenwang, Peter; Naraghi, Hamid; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus
Abstract:  : OBJECTIVES: Patients scheduled for transcatheter aortic valve implantation (TAVI) treatment frequently present with concomitant aortic diseases, in which case they are usually considered to be at high interventional risk and, in particular, unable to undergo the transfemoral TAVI approach. Since the establishment of the 'transfemoral first' strategy for TAVI, there has been an evidence gap with regard to the outcomes of such patients. We aimed to evaluate the mid-term outcomes after transapical TAVI in patients with diverse aortic diseases. METHODS: Fifty-five consecutive elderly patients (78.4 years; standard deviation: 8.6 years) at intermediate surgical risk with severe aortic stenosis and aortic diseases (porcelain aorta 36%, ascending aneurysm 15%, descending aneurysm 26%, type-B dissection 4%, aortic thrombus 7%, Leriche syndrome 4%, aortic kinking 11%, aortic ulcer 2%, previous aortic operation 20%, aortic elongation/tortuosity 4%) underwent transapical TAVI treatment between January 2011 and November 2019 at our institution. We used the second-and third-generation self- and balloon-expanding valves. The follow-up time was 92.6 patient-years. RESULTS: The Society of Thoracic Surgery-Predicted Risk of Mortality score was 7% (standard deviation: 4%). The 30-day mortality and all-stroke rates were 6% and 4%, respectively. The median survival time was 24.9 months (95% confidence interval 17.6–32.3). The median time of freedom from a composite of death and cardio-cerebral adverse events was 24.3 months (95% confidence interval 11.9–36.8). The rate of moderate/severe paravalvular leakage was 2%. The pacemaker rate was 10%. No early or late aortic syndrome occurred. CONCLUSIONS: Transapical TAVI is a safe method and shows very promising early and mid-term outcomes, without early/late aortic syndrome, in patients with aortic diseases for whom transfemoral TAVI as the first-line transcatheter method might be contraindicated or not feasible.